Cooperation Of Indonesia - Iran In The Oil And Gas Energy Sector 2015-2017 - Kamaluddin, Asep; Muhammad Fathun, Laode; Nadirah Rahladhani, Utami (Journal of International Relations on Energy Affairs, 2020)
This research is conducted to discuss about the Cooperation between Indonesia and Iran in oil and gas energy sector period 2015-2017. This research uses qualitative research method with descriptive approach type. The purpose on this research is to explain the shape of cooperation between Indonesia and Iran in oil and gas energy sector. This research also uses bilateral cooperation theory, national interest theory, and energy security concept. From this research, According to the result from this research, the cooperation between Indonesian and Iran in oil and gas energy sector in the period of 2015-2017, the first is Purchasing of Liquified Petroleum Gas (LPG) and Crude Oil form Iran with Competitive Price, second, Oil Refinery Development located in Situbondo (East Java) and the last is Management of Ab-Teymour and Mansouri field. With this cooperation, Indonesia has achieve national interest because the production of oil and gas in Indonesia is increased and the people requirement of oil and gas can be fulfilled. Then in this research, it is also known that the cooperation between Indonesia and Iran in the energy sector will continue even in the wider sector again.